1999
DOI: 10.1046/j.1365-2133.1999.03053.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac involvement and molecular staging in a fatal case of mycosis fungoides

Abstract: Polymerase chain reaction (PCR) amplification of T-cell receptor-gamma gene rearrangement was used for molecular staging in a case of primary cutaneous T-cell lymphoma (CTCL) with fatal evolution. Although initial evaluation was negative for systemic involvement, the patient died due to heart failure. Autopsy findings revealed lymphomatous myocardial infiltration, but other tissues and organs examined, including lymph nodes, liver, spleen, lung and bone marrow, appeared to be free of disease. Molecular analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Although cardiac involvement of lymphoma is rare, 20 autopsy studies of subjects with MF revealed a 15% to 30% incidence of cardiac involvement. [21][22][23] Another study reported gross cardiac involvement in 7 of 12 subjects. 24 Therefore, the potential direct effect of alemtuzumab on T cells residing in the myocardium remains a possibility.…”
Section: Resultsmentioning
confidence: 99%
“…Although cardiac involvement of lymphoma is rare, 20 autopsy studies of subjects with MF revealed a 15% to 30% incidence of cardiac involvement. [21][22][23] Another study reported gross cardiac involvement in 7 of 12 subjects. 24 Therefore, the potential direct effect of alemtuzumab on T cells residing in the myocardium remains a possibility.…”
Section: Resultsmentioning
confidence: 99%
“…Although cardiac involvement of lymphoma is rare, autopsy studies of subjects with MF/SS revealed a 15-30% incidence of cardiac involvement. Therefore, the potential direct effect of alemtuzumab on T cells residing in the myocardium remains a possibility [109].…”
Section: Immunotherapy: New Monoclonal Antibodies In Haematological Mmentioning
confidence: 99%